Prognostic significance of Intracerebral Hemorrhage Score in predicting 30-day mortality in Chittagong Medical College Hospital - Emran, Md Shawkat; Md Hassanuzzaman, -; Majumder, Shiuly; Islam, Md Rafiqul; Kabir, Md Humayun; Hoque Sikder, Abu Bakar Muhammad Nizamul; Majumder, Pijush; Uddin, Syed Arif; Md Rubel, -; Rahman, Md Wahidur; et al. (Bangladesh Journal of Neuroscience, 2019)
Background:Prognosticating the outcome of Intracerebral Hemorrhage (ICH) at the time of admission is important to customize treatment in a cost-effective manner in such cases. ICH sore is a widely used prognosticating tool but yet not evaluated in our setting. This study was aimed to assess the prognostic factors influencing outcome and validating the ICH score for prediction of 30-day mortalityin hospitalized patients with ICH. Materials and methods:This prospective observational study was conducted in Chittagong Medical College Hospital, Bangladesh among 105 consecutively admitted patients aged 18 years and above with a computed tomography evidence of spontaneous ICH. ICH score was calculated soon after confirmation of diagnosis. Primary outcome measure was 30-day mortality after admission. Modified Rankin Scale (mRS) was used to assess outcome at discharge and at 30-day follow up. Results:A total of 104 patients were analyzed. Mean age of this cohort was 59.30±19.91 years. At 30 days all 27 patients with an ICH score of 0 survived, whereas those having scores of 1, 2, 3, and 4 had 5.9%, 33.3%, 46.2% and 88.9% mortality, respectively. ICH score was good for discriminating 30-day mortality with having an area under the ROC curve of 0.886 (95% CI:0.816-0.956; p<0.001]. For patients scoring above 2, the rate of poor functional outcome (mRS score e”4) approaches 100%. On the other hand, 18.5% of patients with score of 0 and 64.7% of patients with a score of 1 are not functionally independent after 30 days. Conclusion:In conclusion, the present study has demonstrated that the ICH score is a strong prognostic indicator of ICH outcomes (30-day mortality and 30- day functional outcome) among hospitalized patients in Bangladesh. Bangladesh Journal of Neuroscience 2019; Vol. 35 (2): 78-85